Efficient and reliable packet transfer protocol for wireless multihop bidirectional communications - Yumi Takaki; Makoto Ando; Keisuke Maesako; Keisuke Fujita; Tomio Kamada; Chikara Ohta; Hisashi Tamaki (International Journal of Distributed Sensor Networks)
In wireless multihop bidirectional communication environment, there is a possibility that packet collision and retransmission owing to the hidden node problem decrease efficiency of throughput. The aim of this article is to achieve efficient and reliable packet transmissions in such environments. To do so, we propose a packet transmission scheme named inter-flow network coding with passive acknowledgment. In inter-flow network coding with passive acknowledgment, it is necessary to optimize the encoding latency and to avoid passive acknowledgment packet collision, so we address these issues in this article. Finally, we also confirm that the inter-flow network coding with passive acknowledgment scheme is effective in terms of the collection ratio and delay through simulations.